HUBUNGAN HIPERURISEMIA, OBESITAS DAN RIWAYAT MEROKOK DENGAN KEJADIAN HIPERTENSI - Amirudin Eso; Muhammad Yusuf Hamra; Adhytya Pratama Ahmadi (Halu Oleo University, 2014)
Hypertension is a common clinical problem. Hyperuricemia, obesity, and smoking history are assumed to have a relationship with hypertension in adult. This study was conducted to figure out the association between hyperuricemia, obesity and smoking history with hypertension. Observational method with cross-sectional approach was used in this study. The study was conducted in Laboratorium Klinik Prodia Kendari. Sixty-two samples consist of men and women aged 18-65 years were taken by quota sampling. Blood pressure, body mass index, and blood chemistry result were collected during medical check-up. Smoking history data was collected with direct interview. Chi-square and binary logistic regression analysis were used to analyze the data (α=0,05). There were 50% hypertensive subjects and 50% non-hypertensive subjects. Hyperuricemia had a moderate association with hypertension (p=0,000; r=0,455). Obesity had a weak association with hypertension (p=0,020 ; r=0,248). Smoking history also had a weak association with hypertension (p=0,022 ; r=0,279). In multivariate analysis with confounding factors, only hyperuricemia that had an independent influence to hypertension (p= 0,00 ; OR 25,4 ; 95% CI 4,1-156,1), followed by HDL abnormality (p=0,04 ; OR=14,15 ; 95% CI=2,3-84,2) and total cholesterol (p=0,02 ; OR=22,4 ; 95% CI=3,2-153,8). Hyperuricemia, obesity, and smoking history, were associated with hypertension. Only hyperuricemia had the independent influence to hypertension.Key words: Hyperuricemia, obesity, smoking history, hypertension